Early Childhood Bilingualism: The Myths, Truths, and Implications in English Language Learning in Pontianak - Teddy Fiktorius (Universitas Ahmad Dahlan, 2020)
The paper explicates the immediate concern of gaining a deeper insight of language acquisition in the early childhood bilingualism in the setting of Pontianak city, a multi-ethnic city located in West Kalimantan, Indonesia. It is written through descriptive method or library research to provide the readers, especially the parents and teachers with better insights into a basis for decision making about raising and educating children bilingually. The first part elaborates on four myths, namely the myth of the monolingual brain, the myth of time investment, the myth of bilingualism and language impairment; and the myth of minority language children. It is followed by the argumentative support by the experts in the fields based on the literature review. Next, discussions are presented as a whole, pointing out some of significant implications for parents and teachers. Finally, an overall conclusion of the paper coverage is provided.